The role of exercise parameters on small extracellular vesicles and microRNAs cargo in preventing neurodegenerative diseases - Fischetti, Francesco; Poli, Luca; De Tommaso, Marina; Paolicelli, Damiano; Greco, Gianpiero; Cataldi, Stefania (Frontiers in Physiology, 2023)
Physical activity (PA), which includes exercise, can reduce the risk of developing various noncommunicable diseases, including neurodegenerative diseases (NDs), and mitigate their adverse effects. However, the mechanisms underlying this ability are not yet fully understood. Among several possible mechanisms proposed, such as the stimulation of brain-derived neurotrophic factor (BDNF), endothelial nitric oxide synthase (eNOS), insulin-like growth factor-1 (IGF-1), vascular endothelial growth factor (VEGF), and nerve growth factor (NGF), the possible involvement of particular vesicular structures enclosed in lipid membranes known as extracellular vesicles (EVs) has recently been investigated. These EVs would appear to exert a paracrine and systemic action through their ability to carry various molecules, particularly so-called microRNAs (miRNAs), performing a function as mediators of intercellular communication. Interestingly, EVs and miRNAs are differentially expressed following PA, but evidence on how different exercise parameters may differentially affect EVs and the miRNAs they carry is still scarce. In this review we summarized the current human findings on the effects of PA and different exercise parameters exerted on EVs and their cargo, focusing on miRNAs molecules, and discussing how this may represent one of the biological mechanisms through which exercise contributes to preventing and slowing NDs.